sdrH enhances Staphylococcus aureus infection in diabetic wounds - Nie, Kaiyu; Wang, Kaiyu; Wen, Yin; Peng, Jinmei; Tang, Shijie (Frontiers in microbiology, 2025)
Diabetes mellitus is a widespread chronic condition that can lead to a variety of complications. Among the numerous complications associated with diabetes, diabetic foot ulcers are particularly notable due to their high prevalence and potential severity. These ulcers are characterized by a substantial incidence rate, a considerable risk of infection, and a high probability of necessitating amputation. , a notorious pathogen within this context, exacerbates wound pathogenesis and can facilitate ulcer extension and, in severe instances, gangrene through the secretion of numerous virulence factors. RT-qPCR was used to analyze the expression of adhesin virulence factors. Utilizing gene knockout techniques to deleted the and genes. Biofilm formation of S. aureus was observed by scanning electron microscope. The effect of and genes on infected wound healing was also evaluated using a diabetic mice skin wound infection model. The gene and the gene cluster are critical contributors to infection in diabetic wounds. Post-infection with the single-gene knockout strain, a significant enhancement in wound healing rates was observed, accompanied by a marked reduction in bacterial colonization per unit area. Conversely, no significant differences were detected between the gene cluster knockout strain and the wild-type strain. Compared to infections caused by either the wild-type strain or the single-knockout strain, infection with the / double-knockout strain led to a marked increase in the wound healing rate and a significant reduction in bacterial load. This study presented that the gene enhances the virulence of in diabetic wounds by attenuating the host immune response, reducing the infiltration of inflammatory cells, and impairing the immune system's capacity to clear bacteria, thereby impeding the wound healing process. Although is not a pivotal player, it seems to enhance the virulence capabilities of .